Bimetallic ions regulate pore size and chemistry of zeolites for selective adsorption of ethylene from ethane. (20th July 2020) - Liu, Yuzong; Wu, Ying; Liang, Wanwen; Peng, Junjie; Li, Zhong; Wang, Haihui; Janik, Michael J.; Xiao, Jing
Graphical abstract: Highlights: Ideal C2 H4 /C2 H6 molecular sieving with record C2 H4 uptake (3.7 mmol/g) is achieved. The pore size of zeolite is controlled precisely in ±0.2 Å increments. C2 H4 stretches for selective admission to pores with aperture <4 Å induced by Ag + . Abstract: The petrochemical industry currently accomplishes olefin/paraffin separation by energy-intensive cryogenic distillation at an enormous scale. We report a sequential Ca 2+ /Ag + ion-exchanged zeolite that achieves nearly ideal molecular sieving of C2 H4 /C2 H6 and superior C2 H4 adsorption capacity. Sequential and partial ion exchange regulates the pore size in ±0.2 Å increments, ranging between 3.8 and 4.2 Å. The demonstrated C2 H4 adsorption capacity of 3.7 mmol/g, under ambient conditions, is the highest among zeolite-based materials. Elaborated with DFT calculations, Ag + -induced the stretching of the C-H bond and reduction of H-C-H bond angle of the C2 H4 molecule in confined pore, providing C2 H4 with the molecular basis and favorable kinetics for selective admission to pore size even less than 4 Å. The strategy of using bimetallic ions to regulate pore aperture size and selective admission of gas molecules with favorable kinetics provides a general path to be extended to other analogous molecular separation processes.